1999
DOI: 10.1093/oxfordjournals.jmicro.a023653
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of age-related changes in mouse olfactory epithelium

Abstract: Transmission and scanning electron microscopic examinations were undertaken to detail changes in the olfactory epithelium (OE) resulting from the ageing process. Samples were prepared from 3% glutaraldehyde/1% formaldehyde perfused mice aged 6 months and 29-30 months. Compared to OE from young adults, a number of striking changes were apparent in tissue from older animals. The most obvious of these were extensive local accumulations of large inclusion bodies, totally disrupting the normal morphology of such af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
7
21
0
Order By: Relevance
“…All procedures were approved by the University of Tokyo Animal Care Committee and carried out in accordance with the National Institutes of Health (NIH) Guide for the Care and Use of Laboratory Animals. Although the mice in each age group appeared to be in good health at the time of sacrifice, we observed spontaneous age-related degenerative changes of the neuroepithelium in some parts of the 16-month-old olfactory mucosa, including an apparent reduction in the number of, or the total loss of, the OMP-positive neurons compared with age-matched normal-appearing olfactory mucosa, as described in our previous studies (Watanabe et al, 2006;Kondo et al, 2009) and those from other laboratories (Loo et al, 1996;Nagano et al, 1997;Rosli et al, 1999;Holbrook et al, 2005). Because the purpose of the present study was to obtain information regarding the age-related changes in cell dynamics under undisturbed conditions, we tried to eliminate the influence of such degenerative parts of the neuroepithelium on the analysis of cell dynamics.…”
Section: Materials and Methods Animalssupporting
confidence: 78%
See 1 more Smart Citation
“…All procedures were approved by the University of Tokyo Animal Care Committee and carried out in accordance with the National Institutes of Health (NIH) Guide for the Care and Use of Laboratory Animals. Although the mice in each age group appeared to be in good health at the time of sacrifice, we observed spontaneous age-related degenerative changes of the neuroepithelium in some parts of the 16-month-old olfactory mucosa, including an apparent reduction in the number of, or the total loss of, the OMP-positive neurons compared with age-matched normal-appearing olfactory mucosa, as described in our previous studies (Watanabe et al, 2006;Kondo et al, 2009) and those from other laboratories (Loo et al, 1996;Nagano et al, 1997;Rosli et al, 1999;Holbrook et al, 2005). Because the purpose of the present study was to obtain information regarding the age-related changes in cell dynamics under undisturbed conditions, we tried to eliminate the influence of such degenerative parts of the neuroepithelium on the analysis of cell dynamics.…”
Section: Materials and Methods Animalssupporting
confidence: 78%
“…Histological studies of the olfactory mucosa in laboratory animals such as mice and rats have shown an age-dependent decrease in neuroepithelial thickness (Walker et al, 1990;Weiler and Farbman, 1997;Watanabe et al, 2006). Spontaneous degenerative changes of the olfactory mucosa, including the loss of mature ORNs and the replacement of olfactory neuroepithelium by respiratory-like ciliated epithelium, progress both in terms of distribution and severity with increasing age (Nakashima et al, 1984;Trojanowski et al, 1991;Loo et al, 1996;Nagano et al, 1997;Rosli et al, 1999;Holbrook et al, 2005;Kondo et al, 2009). These agerelated structural changes in the olfactory neuroepithelium suggest that age could influence the parameters of cell dynamics that regulate neuronal population numbers, such as mitosis of the basal cells, differentiation of neuronal cells, and cell death.…”
mentioning
confidence: 99%
“…In contrast, hyaline lesions of the nasal cavity and respiratory tract identical to those described in our study, have been found in other conventional mice. 11,[22][23][24][25][26] Hyalinosis in gall bladders and in bile and pancreatic ducts has also been reported previously in these same and several other mouse strains or stocks. 11,13,14,[27][28][29] The characteristic pulmonary lesions containing macrophages with eosinophilic crystal formation seen in our 129S4/SvJae population, furthermore, resemble those reported in the motheaten mouse 16,22,30,31 and are sometimes associated with lung tumors 32,33 as well as with macrophage pneumonias in a number of strains.…”
Section: Discussionmentioning
confidence: 54%
“…Consequently, it is normally capable of regenerating the olfactory receptor neurons lost through these processes. This regenerative capacity is lost with age, leading to eventual permanent degradation (Loo et al, 1996;Weiler and Farbman, 1997;Rosli et al, 1999;Conley et al, 2003). Demonstration of a role for the aged OB in olfactory discrimination, therefore, requires elimination of the OE as a possible confound.…”
Section: Aged Mice Demonstrate Impairment In Fine Olfactory Discriminmentioning
confidence: 99%